Hubungan Iklim Komunikasi Organisasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai di Kantor Wilayah Kementerian Agama Provinsi Sumatera Barat - Rahman, Aulia; Arif, Ernita; Darwis, Yuliandre (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
Good communication within an organization will create a harmonious work atmosphere and create work enthusiasm that encourages increased performance of organizational members. On the other hand, leadership factors can influence and move individuals in the organization to achieve maximum performance. This research aims to describe the organizational communication climate, leadership style and employee performance as well as to determine the relationship between the organizational communication climate and leadership style on the performance of employees of the Regional Office of the Ministry of Religious  Affairs  Religious Affairs, both partially and simultaneously. This research is quantitative research with a data collection instrument using a questionnaire distributed to 58 respondents, namely employees of the Ministry of  Religious Affairs using the Stratified Random Sampling method. Processing of research data was carried out with the help of the SPSS program, with data analysis using R correlation analysis and multiple correlation. Based on the data description test, the implementation of communication climate is at 89%, leadership style is at 75.4%, while employee performance is at 85.3%. Meanwhile, the results of the R correlation analysis test on Communication Climate on Employee Performance showed that the correlation coefficient value Rcount ≥ Rtable was 0.399≥0.218 and a significant value of 0.0020.05, which means there is a low relationship between Organizational Communication Climate and Employee Performance. The correlation analysis value of R Leadership Style on Employee Performance obtained a coefficient value of Rcount ≥ Rtable, namely 0.471≥0.218 and a significant value of 0.0000.05, which means there is a moderate relationship between Leadership Style and Employee Performance. The results of the multiple correlation analysis test have a moderate correlation of 0.563 and a significant value of 0.0000.05, which means that there is a positive and significant relationship between organizational communication climate and leadership style on employee performance at the Regional Office of the Ministry of Religious Affairs in West Sumatera.